PENGARUH PENGGUNAAN SPEED HUMPS TERHADAP TINGKAT KEBISINGAN - Argya Jaganaputra; Tri Basuki Joewono (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2011)
Speed humps are speed limiting devices to protect pedestrians and reduce the accident rate. The installation of speed humps in residential can reduce the speed of motorists but, at the same time, also can create a problem. The purpose of this study is to analyze the noise level caused by installation of speed humps and to compare noise levels before and after vehicle crossed the speed humps. The results show that the noise levels caused by vehicles after passing the speed hump are higher that those before the hump. The average noise levels at distances of 50 m and 10 m before the speed hump are 64.15 dBA and 63.63 dBA, respectively. These values increase to 66.64 dBA and 69.89 dBA at distances of 50 m and 10 m after the speed hump. It is also found that the noise levels for different location and time of measurement are significantly different.Keywords: speed humps, noise level, speed limiting device.